1999
DOI: 10.1111/j.1572-0241.1999.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Comparison of Endoscopic Ultrasound- and Computed Tomography-Guided Celiac Plexus Block for Managing Chronic Pancreatitis Pain

Abstract: EUS-guided celiac block provided more persistent pain relief than CT-guided block and was the preferred technique among the subjects studied. EUS-guided celiac block appears to be a safe, effective, and less costly method for controlling the abdominal pain that can accompany chronic pancreatitis in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
1
15

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(122 citation statements)
references
References 30 publications
2
103
1
15
Order By: Relevance
“…Metabolische Effekte wurden bisher nicht im Langzeitverlauf untersucht. vor (Überlegenheit der endosonografischen Steuerung) [336]. Ebenso gibt es Studien zur Frage der endoskopisch ultraschallgesteuerten Plexusblockade mit 1 oder 2 Injektionen (kein signifikanter Unterschied) [337] sowie zum Vergleich der Plexus-coeliacusBlockade mit der Pankreatikogastrostomie (Überlegenheit des chirurgischen Verfahrens) [338] und der endoskopischen Ultraschallsteuerung mit der Röntgen-Durchleuchtung zur Plexus-coeliacusBlockade (Überlegenheit der endosonografischen Steuerung) [339].…”
Section: Leitlinie 1187unclassified
See 1 more Smart Citation
“…Metabolische Effekte wurden bisher nicht im Langzeitverlauf untersucht. vor (Überlegenheit der endosonografischen Steuerung) [336]. Ebenso gibt es Studien zur Frage der endoskopisch ultraschallgesteuerten Plexusblockade mit 1 oder 2 Injektionen (kein signifikanter Unterschied) [337] sowie zum Vergleich der Plexus-coeliacusBlockade mit der Pankreatikogastrostomie (Überlegenheit des chirurgischen Verfahrens) [338] und der endoskopischen Ultraschallsteuerung mit der Röntgen-Durchleuchtung zur Plexus-coeliacusBlockade (Überlegenheit der endosonografischen Steuerung) [339].…”
Section: Leitlinie 1187unclassified
“…Ebenso gibt es Studien zur Frage der endoskopisch ultraschallgesteuerten Plexusblockade mit 1 oder 2 Injektionen (kein signifikanter Unterschied) [337] sowie zum Vergleich der Plexus-coeliacusBlockade mit der Pankreatikogastrostomie (Überlegenheit des chirurgischen Verfahrens) [338] und der endoskopischen Ultraschallsteuerung mit der Röntgen-Durchleuchtung zur Plexus-coeliacusBlockade (Überlegenheit der endosonografischen Steuerung) [339]. Die endoskopische Ultraschallsteuerung scheint für die Plexus-coeliacus-Blockade besser geeignet als die CT-gesteuerte Plexus-Blockade zu sein, wobei 30 % der Patienten nach 24 Wochen noch profitierten gegenüber 12 % nach CT-gesteuerter Punktion [336]. Ob eine einmalige oder zweifache Injektion erfolgt, scheint irrelevant für die Schmerzfreiheit zu sein [337].…”
Section: Leitlinie 1187unclassified
“…EUS-guided CPB is preferred over CT-guided CPB not only because there are fewer side effects [98] but also because of clarity obtained via EUS. CPB can be performed by injection of anesthetics and/or steroids.…”
Section: Eus-guided Celiac Plexus Blockmentioning
confidence: 99%
“…EUS guided celiac plexus block improves pain in about 50% of patients for a period of 3-6 mo [98] . In a prospective randomized study, Gress et al [98,99] compared EUS to CT-guided CPB for the treatment of CP pain and discovered that about 50% of patients in the EUS group had significant pain reduction. In addition, about 40% (8 wk group) and 30% (24 wk group) of the EUS-guided CPB had continued benefit.…”
Section: Eus-guided Celiac Plexus Blockmentioning
confidence: 99%
“…Strong consensus (100 %) An RCT comparing the safety and efficacy of EUS-guided vs. computed tomography-guided CPB in chronic pancreatitis showed that the former was significantly more effective than the latter in short-term (50 % vs. 25 % at 4 weeks) and long-term pain control (30 % vs. 12 % at the end of follow-up) [40]. Another RCT comparing EUS-guided vs. percutaneous fluoroscopyguided CPB with bupivacaine and triamcinolone demonstrated improvement in pain scores (visual analog score) in 70 % of cases in the EUS group vs. 30 % of cases in the percutaneous group [41].…”
Section: Recommendationmentioning
confidence: 99%